2022
DOI: 10.1016/j.isci.2022.103775
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual strategies for characterizing interactions in microbial communities

Abstract: Summary Understanding the sets of inter- and intraspecies interactions in microbial communities is a fundamental goal of microbial ecology. However, the study and quantification of microbial interactions pose several challenges owing to their complexity, dynamic nature, and the sheer number of unique interactions within a typical community. To overcome such challenges, microbial ecologists must rely on various approaches to distill the system of study to a functional and conceptualizable level, allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…To further understand whether the long-term antibiotic treatments induce the network remodeling of the gut microbiota, we performed SparCC co-occurrence network analyses to determine the interactive complexity of bacteria in the microbiota by the number of nodes and edges. 30 We found that although the number of nodes (genus-level taxa) was similar between untreated microbiota (node number = 98) and short-term treated microbiota (node number = 95), the edge number of the short-term treated microbiota was decreased from 399 to 168 ( Figure 3A and B ). Higher modularity was also observed in the short-term treated network, suggesting that the antibiotic treatment disrupted the compact network connections observed in untreated microbiota ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 89%
“…To further understand whether the long-term antibiotic treatments induce the network remodeling of the gut microbiota, we performed SparCC co-occurrence network analyses to determine the interactive complexity of bacteria in the microbiota by the number of nodes and edges. 30 We found that although the number of nodes (genus-level taxa) was similar between untreated microbiota (node number = 98) and short-term treated microbiota (node number = 95), the edge number of the short-term treated microbiota was decreased from 399 to 168 ( Figure 3A and B ). Higher modularity was also observed in the short-term treated network, suggesting that the antibiotic treatment disrupted the compact network connections observed in untreated microbiota ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 89%
“…Pairwise interactions are frequently assumed in constructing dynamical systems models of ecological systems [1][2][3][4]. This is a foundational assumption of classical evolutionary game theory in which the replicator dynamic is built from a matrix game [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, culture-based methods do not capture changes in the ecological structure of the community as a whole, which can provide valuable insights into ecosystem health [ 10 , 46 , 47 ]. Bacterial pathogens and fecal indicator taxa do not exist in isolation, rather, they exist within expansive, interactive communities of diverse and abundant microbial members [ 12 , 24 ]. Therefore, improving our understanding of the relationship between microbiology and water quality may require a more holistic examination of the microbial community.…”
Section: Introductionmentioning
confidence: 99%